Depressive Symptoms and Suicidal Thoughts in Restless Legs Syndrome. Issue 4 (5th January 2022) - Chenini, Sofiene; Barateau, Lucie; Guiraud, Lily; Denis, Claire; Rassu, Ana Laura; Lopez, Regis; Jaussent, Isabelle; Dauvilliers, Yves
Abstract: Background: Whether depression and suicide thoughts relate to restless legs syndrome (RLS) or comorbidities associated with RLS remain unclear. Objectives: To determine frequency of depressive symptoms and suicidal thoughts in patients with RLS and their change after RLS treatment, associated clinical and polysomnographic factors, and current major depressive episode (MDE) frequency and suicide risk in RLS. Methods: Overall, 549 untreated patients with RLS and 549 age‐, sex‐, and education level‐matched controls completed a standardized evaluation, including the Beck Depression Inventory‐II that has one item on suicide thoughts. Patients underwent a polysomnographic recording and completed the Urgency, Premeditation, Perseverance, Sensation Seeking Impulsive Behavior scale. In a subgroup of 153 patients, current MDE and suicide risk were assessed with the face‐to‐face Mini‐International Neuropsychiatric Interview (MINI). A subgroup of 152 patients were evaluated in untreated and treated conditions. Results: The frequency of depressive symptoms (32.5%) and suicidal thoughts (28%) was 10‐fold and 3‐fold higher, respectively, in patients with RLS than controls. Current MDE (10.5%) and suicidal risk (19.9%) (MINI) were also high. Moderate‐to‐severe depressive symptoms were associated with young age, female sex, insomnia symptoms, and urgency dimension. The suicide risk was associated with depression, impulsiveness, and RLS severity. RLS treatment improved depressive symptoms but not suicidal thoughts. Conclusion: The rate of depressive symptoms, depression, and suicidal thoughts/risk was higher in patients with RLS, with key associations with insomnia symptoms, urgency dimension, and RLS severity. These results emphasize the importance of detecting these symptoms in current practice and of evaluating their change after treatment, especially in young women, to improve RLS management. © 2022 International Parkinson and Movement Disorder Society